Characterization of the complete chloroplast genome of Macleaya cordata and its phylogenomic position within the subfamily Papaveroideae. Issue 2 (2nd April 2020) - Dong, Shujie; Gao, Chenshu; Wang, Qirui; Ge, Yuqing; Cheng, Rubin
Abstract: Macleaya cordata (Willd.) is a perennial herb with significant antimicrobial and anti-inflammatory activities. In this study, we report the complete chloroplast genome sequence of M. cordata . The total genome size was 163, 179 bp in length, containing two inverted repeated (IR) regions of 28, 329 bp each, a large single copy (LSC) region of 87, 933 bp and a small single copy (SSC) region of 18, 588 bp. The genome contains 114 genes, including 79 protein genes, 4 rRNA genes, 28 tRNA genes and 3 pseudo genes. The overall GC content of M. cordata is 38.59%, with the highest GC content of 42.79% in IR region. A total of 49 simple sequence repeats are identified in the cp genome of M. cordata . Phylogenetic analysis demonstrated that M. cordata clustered together with M. microcarpa, further forming a monophyletic group with the genuses Hylomecon and Coreanomecon. This work provides basic genetic resources for developing robust markers and investigating the population genetics diversities for this famous medicinal species.